Precision care for Barrett’s esophagus - Triadafilopoulos, George; Friedland, Shai (Translational Gastroenterology and Hepatology; Vol 3 (September 2018): Translational Gastroenterology and Hepatology, 2018)
Modern recognition and management of Barrett’s esophagus, a precursor to esophageal adenocarcinoma depends on diagnostic accuracy, risk assessment, technical expertise and consideration of many options to best tailor therapy for every patient. Concomitant management of acid reflux is essential, frequently with proton pump inhibitors. Ablation and resection favorably affect the evolution towards cancer. Using precision medicine tools, such as imaging, molecular diagnostics and analytics may lead to cost- and comparatively-effective therapies ultimately aiming at cancer prevention. Knowledge of the risk factors for Barrett’s esophagus and progression to dysplasia and cancer can help tailor a precision medicine approach with more aggressive screening and surveillance targeted at patients that are most likely to benefit.